Methods of Resolving Environmental Disputes and Violations of in Vietnam and Recommendations - Lan, Nguyen Thi (VNU Journal of Science: Legal Studies, 2025)
The environment is the sum of factors surrounding humans, affecting the existence and development of humans, creatures, nature and life, economy and society. Therefore, every activity of individuals and organizations in production, business, or daily life directly affects the environment and the objects affected by the environment, thereby giving rise to disputes and violations of environmental laws. So, like other countries in the world, Vietnamese law has formed a system of regulations in the environmental field, creating a legal framework for environmental protection activities and resolving disputes and violations of environmental laws. The article mentions methods of handling violations, resolving environmental disputes, and recommendations for improving environmental protection policies and laws, contributing to making the environment clean and ensuring sustainable development in the process of economic and social development so that our country becomes increasingly prosperous.